2021
DOI: 10.3390/cancers13215392
|View full text |Cite
|
Sign up to set email alerts
|

TP53 in Myelodysplastic Syndromes

Abstract: Myelodysplastic syndromes (MDSs) are heterogeneous for their morphology, clinical characteristics, survival of patients, and evolution to acute myeloid leukemia. Different prognostic scoring systems including the International Prognostic Scoring System (IPSS), the Revised IPSS, the WHO Typed Prognostic Scoring System, and the Lower-Risk Prognostic Scoring System have been introduced for categorizing the highly variable clinical outcomes. However, not considered by current MDS prognosis classification systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 126 publications
(162 reference statements)
0
11
0
Order By: Relevance
“…A consecutive phase 3 study in patients with TP53 mutant MDS failed to meet the primary endpoint of a significantly increased CR rate (Press Releases | Aprea Therapeutics). A comprehensive discussion of ongoing clinical trials in this particular patient cohort has recently been published [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A consecutive phase 3 study in patients with TP53 mutant MDS failed to meet the primary endpoint of a significantly increased CR rate (Press Releases | Aprea Therapeutics). A comprehensive discussion of ongoing clinical trials in this particular patient cohort has recently been published [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…TP53 is a key tumour suppressor gene involved in fundamental biological processes required for genomic stability and is recurrently mutated in a subgroup of MDSs and AML ( 8 ). It has been proven to be an adverse marker in the prognosis of AML and MDS patients and is associated with an increased proportion of blasts in the bone marrow, thrombocytopenia, complex karyotypes, and resistance to lenalidomide, hypomethylating agents, and allo-HSCT, all of which result in poor outcomes for MDS cases with TP53 mutations ( 2 ). Interestingly, recent clinical trials have demonstrated that patients with MDS harbouring TP53 mutations displayed favourable responses to treatment with Dec ( 16 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Complex karyotype; Monosomal karyotype: 45, XY, del(5q) (q15 q35), -6, der (18) (18pter->q21.1::? ::6q11->6qter) [4]/ 44,idem,-3,add(8)(p11.2)[14]/ 43, idem,-3, add(8)(p11.2)-17 [2]/ 46, XY, del(5q), (q15q35),+11,-18 [2]/ 49, XY,del(5)(q15q35),+8,+11,+22 [1] 5q del, trisomy 8 by FISH Complex karyotype: 41-45, XY, ?del(3)(p23),?Inv(3)(?P25?Q23),-5,?Dic(7;20)(p13;q11)[cp16]/42,XY,?Del(3)(q21),-5, -7,?Dic(7;20)(p13;q11),+8,+9,-16,?Del(17)(p11),-18,-19 [1]/45, XY,?Inv(3)(?P25?Q23),-5,?Del(7) (p21),?Dic(7;20)(p13;q11),+22,+r [1]/41,XY,-1?Del(3)(p23),-5,?Del(7)(p13),-10,-18,-20 [1]/46,XY [8] 5q del, 7q del,trisomy 8 by FISH…”
Section: Data Availability Statementmentioning
confidence: 99%
See 2 more Smart Citations